On Appeals to Non-existent Authorities as Arguments from Analogy - Hinton, Martin (Informal Logic, 2021)
Herein, I consider arguments resting on an appeal to a non-existent authority as a species of argument from authority, and ultimately show them to be reliant on arguments from analogy in their inferential force. Three sub-types of argument are discussed: from authorities as yet unborn, no longer living, or incapable of ever doing so. In each case it is shown that an element of arguing from analogy is required since there can be no direct evidence of any assertions of the source. In conclusion, it is suggested that such steps of analogy are employed frequently in traditional arguments from authority.